Applying a gender lens to science, technology and innovation (United Nations New YorkUS, 2011)
Draws attention to the importance of policy coherence across programmes and regulations, the relevance of applying evidence-based and participatory approaches, and the need to conduct regular gender-disaggregated monitoring and evaluation.
Keywords: SCIENCE AND TECHNOLOGY